Assessment of Diabetic Retinopaty Risk Factors in Type II Diabetes Mellitus - Desy Anggraini; Yani Sofiani; Ninik Yunitri; Fitrian Rayasari (GLOBAL HEALTH SCIENCE GROUP, 2025)
Diabetic retinopathy (DR) is a leading microvascular complication of diabetes mellitus (DM), primarily caused by chronic hyperglycemia. It leads to vascular occlusion, increased vascular permeability, retinal abnormalities, and detachment, ultimately resulting in visual impairment and blindness. Implementing Evidence Based Nursing Practice using diagnostic tests to determine the sensitivity and specificity of the assessment instrument for Diabetic Retinopathy Risk Factors in Type II DM Diagnostic tests are descriptive observational studies with a cross-sectional study design. This application is classified as descriptive observational because only observations are made without any intervention (treatment). The test is carried out with ROC where to see the sensitivity and specificity of the application instrument. The results of the analysis showed that the sensitivity of the application of the assessment of diabetic retinopathy risk factors using the ROC Curve Test was 100%. Meanwhile, the specificity of the instrument for the application of the assessment of diabetic retinopathy risk factors was 81.3%. The application of diabetic retinopathy risk factor assessment can be used to assess the risk of diabetic retinopathy because it has good sensitivity (%) and specificity (%) values. However, when applying the diabetic retinopathy risk factor assessment, only the risk value of diabetic retinopathy was obtained where the application patient did not experience complaints and decreased visual acuity.